A newly developed rapid uniform thermal cycle test system for electronic components. (November 2017) - Ikuno, Hajime
Abstract: Electronic components are difficult to heat or cool uniformly and rapidly because of the low heat conduction properties of the materials used in these components. The present study reports a new rapid thermal fatigue test system that circulates a temperature-controlled air shower around test samples to realize both uniform and rapid temperature control. Since the proposed test system allows multi-unit integration of multiple test chambers, the simultaneous evaluation of several samples under various test conditions can be performed efficiently. Based on the results of the temperature profile measured for a practical electronic circuit board, the proposed system is confirmed to enable the target temperature to be approached rapidly while maintaining a uniform temperature distribution. The proposed system shortens the thermal cycle period from 60 min to 12 min while generating the same degree of crack damage and the same fracture mode of solder joints.